anonymous
  • anonymous
I'm trying to solve this using the elimination process: 3x+(5/2)y=21 x+2y=14 have i done it right so far? I'm new to the elimination process.. 3x+(5/2)y=21 -(x+2y=14) 2x + 1/2y = 7
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
katieb
  • katieb
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
texaschic101
  • texaschic101
no... lets get rid of the fraction in the first equation by multiplying it by 2.. (2)3x + (2)5/2y = (2)21 6x + 5y = 42(thats better) Now the problem reads.... 6x + 5y = 42 x + 2y = 14 --->(-6)x + 2y = 14 ------------- 6x + 5y = 42 -6x - 12y = - 84 (result of multiplying by -6) --------------add 0 - 7y = - 42 -7y = - 42 (divide by -7 to get y by itself) -7y/-7 = -42/-7 y = 6 now sub 6 in for y in either of the original equations... x + 2y = 14 x + 2(6) = 14 x + 12 = 14 (subtract 12 from both sides to get x by itself) x + 12 - 12 = 14 - 12 x = 2 now check by subbing in your known variables... x + 2y = 14 2 + 2(6) = 14 2 + 12 = 14 14 = 14 (correct) What you have to try to do in elimination is eliminate " get rid of " one of the variables, so you can find the other variable. Sometimes you have to do this by multiplying the equation by a number so that the variables will cancel each other out. That is why I multiplied the second equation by a -6. And as you can see, it made the x's cancel out and I was able to solve for y. Once finding y, I then substituted what I got for y into the second equation and found x. You can substitute into either one of the equations and you will get the answer. Then I checked my answer by subbing in the known variables and if they equal, which they did, then the problem is correct.
anonymous
  • anonymous
Thank you ! (:
texaschic101
  • texaschic101
your quite welcome....thats what I am here for

Looking for something else?

Not the answer you are looking for? Search for more explanations.